Climate change sustainability: From bargaining to cooperative balanced approach - Tiziana Ciano; Massimiliano Ferrara; Mariangela Gangemi; Domenica Stefania Merenda; Bruno Antonio Pansera (Games, 2021)
This work aims to provide different perspectives on the relationships between cooperative game theory and the research field concerning climate change dynamics. New results are obtained in the framework of competitive bargaining solutions and related issues, moving from a cooperative approach to a competitive one. Furthermore, the dynamics of balanced and super-balanced games are exposed, with particular reference to coalitions. Some open problems are presented to aid future research in this area.
Keywords: C70; C78; C60; 330; balanced and super-balanced games; climate change; competitive bargaining sets; non-empty core; sustainability